Microbial contamination of Lettuce (Lactuca sativa) and soil profile in Kirkuk regions under controlled application of domestic wastewater - Rakan Hussein; Shahad Bahedh; Fatema Abdul Aziz; Maysaa Ali (Microbes and Infectious Diseases)
Background:  In arid countries, the growing scarcity of potable water causes untreated wastewater to be used for crop production, but improper irrigation techniques could pose a serious risk of sewage water contamination of plants, soils, and groundwater, This study was prompted by the increasing risk of harmful bacterial contamination in vegetable crops and groundwater due to the application of wastewater on land.  Methods: The purpose of the study was to investigate (1) how field-grown lettuce plants' microbial contamination is affected by irrigation with untreated wastewater; (2) Fecal coliform bacteria contamination of agricultural soil. From the wastewater flowing in the Al-Khasa River and from the waters of the Lower Zab River in the city of Dibs, Kirkuk Governorate, Iraq. Lettuce plants were grown in two different locations.  Results: Bacterial isolates were extracted from wastewater and plants, Alcaligenes faecalis, Burkholderia gladioli, Enterbacter kobei, Enterbacter hormaechei, Enterbacter ludwigii, Enterococcus columbae, Escherichia coli, Globicatella sulfidifaciens, Klebsiella oxytoca, Klebsiella pneumonia, Morganella morganii, Pseudomonas otitidis, Pantoea agglomerans, Sphingomonas poucimobilis, Staphylococcus lentus and Staphylococcus sciuri. Total bacterial isolates 38  (63.16 %  isolation from wastewater running in khasa river, 5.26 %  isolation from lower zab river and  31.58%  isolation from plant irrigated with wastewaters ). Bacteria were detected per 100 g of dry matter and compared with the control. In order to detect fecal coliform, a sample of the soil profile was also taken at a precise distance of 3 cm from the soil surface. The findings showed that when soil is irrigated with water from the lower Zab River, the number of all bacterial species has significantly decreased. The higher the percentage of wastewater in the irrigation water, the higher the bacterial count/g of the plant root system. By measuring BOD, COD , pH, , chloride, ammonia, conductivity, suspended particles, total dissolved solids, lipids, phosphate, nitrite, and , nitrate.  Conclusion: Each step of pollution levels in the untreated wastewater of the Alkhasa River was examined, and comparisons with the lower Zab River were made and Human behavior and natural processes.